GAIA - a unified framework for sediment transport and bed evolution in rivers, coastal seas and transitional waters in the TELEMAC-MASCARET modelling system. (January 2023) - Tassi, Pablo; Benson, Thomas; Delinares, Matthieu; Fontaine, Jacques; Huybrechts, Nicolas; Kopmann, Rebekka; Pavan, Sara; Pham, Chi-Tuan; Taccone, Florent; Walther, Régis
Abstract: In rivers, coastal seas and transitional waters, sediment transport processes involve a variety of interacting factors that dynamically vary over time and space. The flow dynamics within these highly heterogeneous natural systems influences the spatial patterns of erosion and deposition of the bed sediments, which in turn shapes and conditions the bottom morphology. By taking advantage of the established modelling framework in both two- and three dimensions for unstructured meshes proposed within the Telemac-Mascaret system, the new module Gaia provides a code structure for solving sediment transport and morphological evolution problems. By a clear treatment of sedimentary processes that happen in the water column, in the bed structure, and at the water–bed interface, Gaia efficiently manages the spatial and temporal variability of sediment size classes, properties and transport modes for two- and three dimensions. In addition, this module can easily be expanded and customised to particular requirements by modifying user-friendly, easy-to-read, and well-documented FORTRAN-90 subroutines. Highlights: A new sediment transport and morphological evolution module GAIA, is proposed for the TELEMAC-MASCARET system. It aims at replacing the existing module SISYPHE. Its generalised framework enables any combination of multiple size classes for both non-cohesive and cohesive sediment to be modelled simultaneously. The full compatibility between 2D and 3D sediment transport processes is ensured.